Gangguan Komunikasi Verbal Dengan Terapi Aiueo: Laporan Kasus Pasien Pasca Stroke - Harista, Dessy Rindiyanti; Jatimi, Atika; Fatah, Abdul (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Post-stroke patients experience decreased physical function characterized by difficulty speaking such as slurred speech, aphasia, difficulty expressing feelings through words, and damage to other physical functions due to nerve damage. This triggers the emergence of problems with verbal communication disorders in patients after a stroke. This research aims to carry out the nursing care process for post-stroke patients who experience verbal communication disorders with five stages starting from assessment, establishing a nursing diagnosis, determining nursing interventions, and implementing the nursing plan to the final stage, namely nursing evaluation. Two post-stroke patients were interviewed and observed 7 times over 2 weeks from 28 October 2023 to 10 November 2023. Post-stroke patients were given AIUEO therapy 7 times with the results of the evaluation on the last day showing a marked improvement in the individual's health condition. With increased speech ability, improved behavioral responses, increased hearing ability, decreased aphasia, and decreased speech. The research results were assessed based on the results criteria stated in the Indonesian nursing output standards with interpretation of resolved problems.